Toleransi Beragama: Sebuah Wujud Nyata Program Moderasi Beragama Di Sekolah Dan Madrasah - M. Nasihuddin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Religious moderation education which is being promoted by the Indonesian government through the Ministry of Religion's medium-term program carries three elements, one of which is religious tolerance. The teaching of religious tolerance is conveyed in various educational institutions, both schools under the auspices of the Ministry of Education and Culture, and madrasas under the auspices of the Ministry of Religion. This article was written in order to explore how the teaching of religious tolerance is carried out in schools and madrasas. Civics teachers and PAI teachers are considered to be representatives of religious tolerance learning at the school. This research uses a qualitative method with a phenomenological approach. And the results of the research illustrate that schools and madrasah try to provide the best tolerance education for their students.